Safeguarding women at work? Lessons from Aotearoa New Zealand on effectively implementing domestic violence policies. (September 2021) - Weatherall, Ruth; Gavin, Mihajla; Thorburn, Natalie
Although domestic violence is increasingly acknowledged as a workplace issue and a gender equality issue, a gap remains in the effective implementation of domestic violence policies in workplaces. The Domestic Violence – Victims Protection Act passed in 2018 in Aotearoa New Zealand was a global landmark for holding workplaces accountable for safeguarding victims through a codification of employer responsibility. While the legislation is a milestone, such moves are nascent compared with other workplace gender equality initiatives. In this article, we assess 'where we are now' in relation to domestic violence policy initiatives, arguing that knowledge necessary for successful policy implementation is limited by the historical 'gender blindness' of industrial relations scholarship. For successful implementation, scholars and practitioners must understand domestic violence as a public issue embedded in broader patterns of gender inequality, reinforced by a gendered labour market. Drawing upon vignettes of victims' experiences from empirical data on intimate partner stalking in Aotearoa New Zealand, a research and practice agenda is proposed to consider 'where to next' for implementing domestic violence policies. Our agenda proposes recognising domestic violence as a gendered, public issue which blurs boundaries between work, home and society in order to truly safeguard women at work.